(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Mosquito coil fumes (MCF) is used in several Nigerian homes and some part of the world with reported grave consequences to the respiratory tract majorly. There is paucity of information on its outcome on the gastrointestinal tract being a related organ to the respiratory tract. Forty five male Wistar rats (123.1 ± 7.3g) were used in this study, they were grouped into 3 (n=15/group; 5 each day of experiment). Rats in group 1 served as control (no MCF). Groups 2 and 3 were exposed to MCF for 8-10 h daily for 2 (2p) and 6 (6p) weeks respectively, in a well-ventilated room of 38.3m3 in size each day. After the period of exposure, chronic gastric ulcer were induced by intraluminal application of 50% acetic acid. The animals were sacrificed on days 0 (no ulcer induction), 3 and 10 post ulceration for complete blood count and ulcer scores. Stomach was excised for histology and biochemical assays, homogenized gastric tissues were analyzed by spectrophotometry for malondialdehyde (MDA), catalase and nitric oxide (NO) estimations. Data were expressed as mean ± SEM. Gross ulcer area (mm3) increased significantly on days 3 and 10 in 6p (167.3±16.03; 65.20±3.93) and 2p (152.7±6.20; 68.70±3.45) compared to control (93.26±2.80; 34.82 ±1.84) respectively. Lymphocytes count (%) decreased significantly on day 3 in 2p (60.60 ±1.97) compared to control (70.60 ± 0.87), Neutrophil count (%) in 6p (36.40 ±1.08: 30.20 ±1.46) increased significantly compared with control (25.60±0.80; 26.00 ±1.58) on day 3 and 10 respectively. MDA concentration in 6p and 2p increased significantly compared to control on day 3. Nitric oxide decreased significantly in 6p and 2p on day 3and 10 compared to control. Mosquito coil fumes proofs toxic to the stomach especially to inflamed rats stomach by delaying healing of gastric ulcer through reduction in NO and raised oxidative stress markers.